Processed bed elevation picks from airborne radar depth sounding across the region of three tributaries of Slessor Glacier, Coats Land, East Antarctica (2001/02 season) - Rippin, David; Bamber, Jonathan; Siegert, Martin; Vaughan, David; Corr, Hugh (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2020)
During the austral summer of 2001/02 five thousand line kilometres of airborne radio echo sounding and aeromagnetic data were collected in the region of three tributaries of Slessor Glacier, East Antarctica, which drains into the Filchner Ice Shelf. We present here the processed bed elevation picks from airborne radar depth sounding acquired using the BAS aerogeophysicaly equipped Twin Otter aircraft. Data are provided as XYZ ASCII line data. Data were collected as part of UK Natural Environment Research Council (NERC) grant GR3/AFI2/65 : Radar data are presented in Rippin et al. (2003, 2006) along with further details of survey design, data collection and data processing. Data provided here includes picks of surface and ice sheet bed elevation. Channel definitions: Basic Channels Date: UTC date (YYYY/MM/DD) Time: UTC time (HH:MM:SS.SS) FlightID: Sequential flight number and survey ID e.g. W12 Lon: Longitude WGS 1984 Lat: Latitude WGS 1984 x: x projected meters * y: y projected meters * Radar surfElev: Surface elevation (m) bedElev: Ice bed elevation, derived by subtracting tice from surfElev (m) tIce: Ice thickness (m) * Projected coordinates (x and y) are in Lambert conic conformal with two standard parallels defined as follows: Latitude of false origin: -74.018118 Longitude of false origin: 179 Latitude of 1st standard parallel -72.66666666667 Latitude of 2nd standard parallel -75.33333333333 False easting 1444000 False northing 1123000